Analisis Kesulitan Membaca Pemahaman Siswa Kelas III SDN Tegal Kidongdong Sebagai Alternatif Pembuatan Media Pembelajaran Menemukan Pesan Moral Pada Teks Dongeng - Faijah, Ika Nur; Wardana, Deni; Widjojoko, Widjojoko (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Comprehension reading is activity to absorb information from reading material, understand, know the meaning or implied meaning of reading. In the world of education, especially in elementary school, reading skills are very important in addition to the other three language skills. Of the four language skills that must be mastered by students, most of the difficulties experienced by students are difficulties in reading comprehension. Difficulty in reading comprehension will hinder students in absorbing the information presented in the form of reading in the form of books, magazines, newspapers, documents and others. This study aims to find out, analyze and describe the difficulties experienced by students in reading comprehension on fairy tale texts in class III SDN Tegal Kidongdong in the 2021/2022 academic year and make learning media in the form of animated videos based on the difficulties experienced by students. This study uses a qualitative approach with content analysis method which aims to analyze the phenomenon based on the documents obtained from the research. The subject of this research is a document in the form of student worksheet answers. Data collection techniques used in this study were participant observation, in-depth interviews and document analysis. The results of this study are the difficulties experienced by students, namely difficulties in reading comprehension with a literal level of understanding, namely finding the characteristics possessed by characters in fairy tales, then difficulty in reading comprehension with a literal level of understanding, namely finding paragraphs that show moral messages and finally having difficulty reading comprehension with the level of understanding of interpretation, namely finding the moral message in the fairy tale. Based on the knowledge of these difficulties, the researchers considered it to make learning media in the form of animated videos to be accessed by all third grade elementary school students.